SAFETY CLIMATE ON SMALL AND MEDIUM ENTERPRISES IN BATIK PRODUCTION BASED ON FACTOR ANALYSIS (Journal of Technology and Operations Management, 2022)
Safety climate is an instrument to determine workers' perceptions of occupational safety and health. To find out workers' perceptions about the importance of safety climate factors in the batik industry, it is necessary to do a factor analysis. Factor analysis was carried out using Exploratory Factor Analysis to reduce variables to form new factors with a minimum of lost information. Furthermore, the Kruskal-Wallis test was conducted to determine the differences in the perception of respondents' criteria regarding the previously formed safety climate factors. This study reduces the 8-variable questionnaire with 36 statement items into seven new factors, namely management commitment and worker actions toward safety, management procedures regarding safety, management support for safety, management and worker's efforts to create safety, worker's attitudes regarding work and safety, workers rewards for reporting a hazard, and workers knowledge of safety.